Impact of open educational resources in higher education institutions in spain and latin americas through social network analysis - Piedra Pullaguari, N. (2013)
The modernization of the European education system is allowing undertake new missions such as university responsibility. Higher education institutions have felt the need to open and provide educational resources. OpenCourseWare (OCW) and Open Educational Resources (OER) in general contribute to the dissemination of knowledge and public construction, providing a social good. Openness also means sharing, reuse information and create content in an open environment to improve and maintain the quality of education, at the same time provide an advertising medium for higher education institutions. OpenCourseWare Consortium himself and other educational organizations stress the importance of taking measurement and evaluation programs for an institution OCW. Two main reasons are argued: Allow monitoring the usefulness and usability of Open Educational Resources (OER) and the efficiency of the publishing process, helping to identify and implement improvements that may be relevant over time. Measure the use and impact of the parties involved in the OCW site helps ensure their commitment. This paper the authors evaluate social network analysis like a technique to measure the impact of open educational resources, and shows the results of applied this kind analysis in OpenCourseWare Spanish and Latin American, trying to tackle the above problems by extending the impact of resource materials in the new innovative teaching strategies and mission of university social responsibility providing updated information on the impact of OCW materials, and showing the true potential inherent in the current OCW repositories in Latin American universities. To evaluate the utility of Social Network Analysis in open educational resources, different social networks were built, using the explicit relationships between different participants of OCW initiatives, e.g. co-authorship, to show the current state of OCW resources. And through the implicit relationships, e.g. tagging, to assess the potential of OCW. To measure the impact of OCW, the social relationships, drawing from the information published by universities of Spain and Latin American, between OCW actors are described and assessed using social networks analysis techniques and metrics, the results obtained let to: present a current state of OCW in Latin America, know the informal organization behind the OCW initiatives, the folksonomies arise from using tags to describe courses, and potential collaborative networks between: universities, professors linked to production of OCW. © American Society of Engeneering Education, 2013.